The Role of Blockchain Technology in Securing Supply Chain Information Systems - Maimun; Sufyan (STMIK Indonesia Banda Aceh, 2024)
This research aims to analyze the role of blockchain technology in securing supply chain information systems. The research method used involves literature study and qualitative analysis of blockchain implementation in the context of existing supply chain information systems. The research results show that blockchain technology can play an important role in strengthening the security and integrity of supply chain information systems. By using characteristics such as decentralization, transparency, and reliability, blockchain can help fight security threats such as cyberattacks, counterfeiting, and data manipulation. Through the use of blockchain, information can be secured, verified and safely accessed by stakeholders in the supply chain. Apart from that, blockchain can also increase efficiency and accountability in supply chain information systems. In conclusion, blockchain technology has significant potential in securing supply chain information systems and can contribute to increasing trust between stakeholders.